Durable direct ethanol anode-supported solid oxide fuel cell. (1st August 2017) - Steil, M.C.; Nobrega, S.D.; Georges, S.; Gelin, P.; Uhlenbruck, S.; Fonseca, F.C.
Highlights: Direct ethanol anode-supported SOFC stable for 600 h without water. High-performance SOFC exhibiting similar current output in both hydrogen and ethanol. Ceria-based catalytic layer ensures ethanol conversion and avoids carbon deposits. Abstract: Anode-supported solid oxide fuel cells accumulating more than 700 h of stable operation on dry ethanol with high current output are reported. A highly active ceria-based catalytic layer deposited onto the anode efficiently converts the primary fuel into hydrogen using the electrochemically generated steam. On the other hand, standard fuel cells without the catalytic layer collapse because of carbon deposit formation within the initial 5 h of operation with ethanol. The nanostructured ceria-based catalyst forms a continuous porous layer (∼25 µm thick) over the Ni-based anode support that has no apparent influence on the fuel cell operation and prevents carbon deposit formation. Moreover, the catalytic layer promotes overall steam reforming reactions of ethanol that result in similar current outputs in both hydrogen and ethanol fuels. The stability of single cells, with relatively large active area (8 cm 2 ), confirms the feasibility of a catalytic layer for internal reforming of biofuels in solid oxide fuel cells. The experimental results provide a significant step towards the practical application of direct ethanol solid oxide fuel cells.